The Sentence Processing Analysis of Deaf Students at Sekolah Luar Biasa Negeri Gunungsitoli - Afore Tahir Harefa; Feliks Rejeki Sotani Zebua; Grace Marthini Waruwu; Puspa Fati Handayani Gulo (Journal on Education, 2023)
This study aims to investigate the sentence processing of deaf students at Sekolah Luar Biasa Negeri Gunungsitoli. Through qualitative methods with interviews and observations, the findings show that visualizations, such as pictures and physical objects, greatly help deaf students understand sentences. However, students have difficulty in understanding passive sentences and the concept of phrases. Teaching methods that emphasize visual aspects and individualization are recognized as important factors in improving students' comprehension. The results of this study contribute to the understanding of deaf students' barriers and needs in the learning process. Practical implications include the development of more adaptive teaching methods, while scientifically, this study supplements the knowledge of sentence processing strategies in deaf students. In conclusion, a better understanding of sentence processing by deaf students can contribute to the inclusive approaches in special education.